Case Study on Soft Soil Improvement using Innovative and Cost-Effective Reinforcing Techniques - Susila, Endra; Agrensa, Fico (ITB Journal Publisher, LPPM ITB, 2015)
This paper describes, discusses and compares three new innovations of reinforcement systems for soft soils: (a) a combination of gridded matrass and piles of bamboo, (b) a combination of matrass and piles of bamboo, and (c) a group of mini piles connected by small H-beams with a compacted top layer to hold the top mini piles. First, illustrations and applications of the three types of reinforcement are described from three full-scale field works. Technical bases for the three types are presented, while technical comparisons are discussed next. Finally, conclusions are developed. The case studies, analysis results, and full-scale fieldwork verifications show that the three reinforcement systems have worked properly. Each system has its own advantages and disadvantages in terms of construction duration and cost, capability/effectiveness and material availability, especially in rural areas.